Anatomical and micromorphological characteristics of Pogostemon heyneanus Benth. (Lamiaceae) - AMALIA AMALIA; NORAINI TALIB; JALIFAH LATIP; AMINAH ABDULLAH; ISMAIL BIN SAHID (Universitas Syiah Kuala, 2023)
Foliar micromorphological and anatomical characteristics of Pogostemon heyneanus Benth. (Lamiaceae) was investigated in order to describe its comprehensive characterization and its association with the presence of essential oils. The methods used in this study involved several methods such as cross-section using a sliding microtome and epidermal peeling that were observed under light microscope, and foliar micromorphological characteristics that were observed under scanning electron microscope (SEM). Results showed leaf anatomical and micromorphological characteristics that could be useful in species identification and the localization of chemical properties. The leaf epidermal surfaces were characterized by curved to sinuous anticlinal walls (adaxial side) and sinuous anticlinal walls (abaxial side). The diacytic and anisocytic types of stomata were present only on the abaxial surface. The features of the stem is quadrangular and the well-developed collenchyma function. The sclerenchyma cells are present as clusters at the outer layer of vascular bundles and continuously surround the vascular tissue. Then, there were three forms of crystals found, namely star shaped crystals, prismatic crystals and raphides in the pith area. Eight types of trichomes were observed: simple unicellular, simple multicellular, peltate, short-stalked capitate (unicellular head), short-stalked capitate (bicellular head), short-swollen multistalked (unicellular acute head), long-stalked capitate, and long-swollen stalked capitate (disk head) trichomes. The presence of various glandular trichomes on the leaf surfaces may serve as secretory sites where secondary metabolites or essential oils are produced. The findings on the foliar and stem anatomical and micromorphological characteristics are very useful for the medicinal herbs industry as well as being of taxonomic value.